Imprensa e opinião pública no Brasil Império: Minas Gerais e São Paulo (1826-1842) - Luciano da Silva Moreira (2011)
This dissertation focuses on the relationship between the press and the political life in Imperial Brazil. More strictly, it focuses on the provinces of Minas Gerais and São Paulo, between the years 1826 and 1842, when the press became politically more active, thus contributing to the shaping of society and Imperial State. Although it is mostly concerned with the period limited by those years, the present dissertation breaches those limits, moving backwards to colonial times and forwards to the Second Empire. The thread that binds the dissertation is the hypothesis that the press itself was a decisive happening for the creation of novel historical conditions which brought about the appearance of a network of relations between regional elites and the resulting political strategies which were important for the development of the Imperial State. Initially, this dissertation examines the subjects of and the spaces where the historical plot developed and presents the sociopolitical context of the provinces of Minas Gerais and São Paulo in the first half of the 19th century. Such period comprehends the transformations that followed the coming of Dom João VIs court to Brazil and the liberal movements of the beginning of Dom Pedro IIs reign. The political and economic situation of those provinces as well as their relationship with the court allowed for an atmosphere of debate and the high mobility promoted by the roads that interconnected the regions of the Empire. It is by understanding the role played by those roads that we seek to understand the workings of the communication network that sustained the political debate during the Empire. Next, it addresses the formation of a public sphere of power, following the route of the old typography shops and examining the products of their printing presses. A variety of press-related practices are analyzed and special attention is given to the processes of production and distribution. It then addresses how political writers aspired to attract the public gaze, that is, how they sought to create an alleged public opinion. In doing so, it considers the material nature of printed products and the structuring of a communications network connecting writers and readers from all over the Empire. This dissertation concludes, after assessing the communications network of the periodicals of Minas Gerais and São Paulo, with an analysis about the notion of public opinion and the how it was conceived and idealized in the print products of the afore mentioned provinces.